INFORMATIVE SYSTEM OF EDUCATIONAL PURPOSE FROM MATHEMATICS AS A WAY OF PROFESSIONAL ORIENTATION OF TEACHING STUDENTS IT SPECIALTIES - Lyudmyla Shishko; Iryna Chernenko; Evgenii Kozlovsky (Kherson State University, 2016)
The current state of formation of mathematical knowledge in universities insufficiently focused on their further use in professional activities. Students not formed the ability to apply mathematical knowledge to study general professional and special disciplines. In this article: - considered features of formation of a professional orientation of teaching mathematics using structured content multimedia information system for educational purposes (MISEP); - found psychologo-pedagogical features of teaching mathematics of students IT specialties; - considered methodical aspects of MISEP in teaching the course "Discrete Mathematics" for students of IT specialties